2007
DOI: 10.1111/j.1365-3032.2007.00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect pathways of fitness‐impact in a protozoan‐infected kissing bug

Abstract: Parasites can reduce host fitness through short‐term mortality, complete or partial castration, or slight reductions in host fecundity. Hosts may reduce reproductive effort as an adaptive strategy to tolerate parasitism. However, host fitness reduction may be unrelated to host adaptation but represent a pathological side‐effect of infection. The present study evaluates experimentally the direct and indirect impact of the protozoan parasite Trypanosoma cruzi on the investment of female kissing bugs in reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…[15][16][17][18][19][20] This idea is mainly based on studies of the triatomine species Triatoma infestans. 15,[21][22][23][24][25][26][27] Investigations into the effect of T. cruzi infection on other triatomine species have yielded variable results, with some results suggesting that T. cruzi reduces triatomine survival and or reproduction, [28][29][30][31][32] and others finding little to no effect. [33][34][35] Although some of the discrepancies may be due to differences in experimental conditions or design, it is also possible that the inherent variability of T. cruzi itself is a driver of the variable fitness outcomes in infected triatomines, as it is in its mammal hosts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20] This idea is mainly based on studies of the triatomine species Triatoma infestans. 15,[21][22][23][24][25][26][27] Investigations into the effect of T. cruzi infection on other triatomine species have yielded variable results, with some results suggesting that T. cruzi reduces triatomine survival and or reproduction, [28][29][30][31][32] and others finding little to no effect. [33][34][35] Although some of the discrepancies may be due to differences in experimental conditions or design, it is also possible that the inherent variability of T. cruzi itself is a driver of the variable fitness outcomes in infected triatomines, as it is in its mammal hosts.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this has not been tested, as all published studies on the effect of T. cruzi on triatomines have been limited to one T. cruzi strain-I triatomine species system. 15,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Given that a principle focus in Chagas disease prevention is the interruption of T. cruzi transmission by triatomine bugs living in and around human homes, it is important to understand the full range of outcomes that trypanosome infection can have on triatomines. Therefore, we asked, does variability exist in the effect of different T. cruzi strains on its triatomine host?…”
Section: Introductionmentioning
confidence: 99%
“…Parasite‐induced changes in host body size may be the proximal factor involved in host fitness reduction. Previous studies have reported that the protozoan T. cruzi has a strong impact on several life history traits of M. spinolai (Botto‐Mahan, ; Botto‐Mahan, Cattan, & Medel, ; Botto‐Mahan et al., ). In this study, infected females reached smaller size at maturity compared to those uninfected, suggesting that like other parasite species, T. cruzi probably curtails essential nutrients involved in host growth (Hurd, ; Thompson, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, infected insects show longer developmental time and reduced body weight compared to uninfected insects (Botto‐Mahan, ). Likewise, gonads of infected females have 36.7% less weight than those of uninfected females (Botto‐Mahan, Ossa, & Medel, ). Here, we inquire into the importance of male and female infection costs on host reproduction using an experimental design that permits the assessment of additive (independent) and nonadditive (interactive) effects on host reproductive success.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, we compared how both sexes in the adult stage differ in their investment to traits related to the same functions indicated above, but we also included fecundity. Thus, for the fecundity function, we measured abdominal length as this is a proxy of fecundity in insects (Preziosi et al, 1996) and triatomines (Botto-Mahan et al, 2008). For comparative purposes, we also measured immature abdominal length.…”
Section: Introductionmentioning
confidence: 99%